USING THE TECHNIQUES OF SCHEDULING THE PRODUCTION PROCESSES AND SUPPLY CHAIN MANAGEMENT IN THE FOGGY ENVIRONMENT; APPLIED RESEARCH OF THE ELECTRONIC PRODUCTION PLANT AT AL - ZAWRA GENERAL COMPANY – IRAQ - Abidalreda. N, Yosif; Al-Sammarraie B.Z, Hasan (International Journal of Supply Chain Management, 2019)
This paper gives an overview of the theory and practice of planning and scheduling in supply chains. For this purpose it seeks to solve the problem of loading the machines in the electronic production plant at Al-Zawra General Company, in the case of having more than one order at the same time, one of them within the overall plan (MPS), which in turn was the result of "the overall planning using its various strategies and other sudden orders and emergency outside the total plan, which is forced to work overtime and regular and how to deal whit hit within the rules of scheduling production processes in the foggy environment. The goal of the research is to find a mechanism for working in the plant in case the three levels of total planning progresses, and which begins with forecasting the demand in the foggy environment, and fixing them in order to obtain accurate results to build on them the overall plan in preparing the necessary resources for production according to the product structure (BOM) reaching to scheduling different fixed and working operations using scheduling rules on one machine (FCFS, LPT, SPT), in addition to identifying a mechanism that works regularly on the distribution of orders on the business through the fixed and multiple scheduling in the foggy environment and choosing the optimal strategy for action. In order to achieve this, the researcher used the MATLAB in designing the databases using two types of artificial intelligence algorithms (TOPSIS, SPEAII), which provide multiple decision-making criteria through which she could find the best solution for the sequential work on machines, which reduced the time of achievement and reduced the four kinds of costs which are (cost of production, cost of scheduling, cost of storage, cost of subcontractor, the cost of extra work and unemployed).